PERLINDUNGAN KONSUMEN TERHADAP PENGGUNAAN E-LIQUID DALAM ROKOK ELEKTRIK DI INDONESIA DAN INGGRIS - Zaldi ` Nasrudin (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Zaldi Nasrudin, Yuliati, Shinta Puspitasari Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 Malang e-mail: zaldinasriudin@student.ub.ac.id   ABSTRAK Tulisan ini mengangkat permasalahan tentang perlindungan konsumen terkait penggunaan e-liquid dalam rokok elektrik di Indonesia dan Inggris. Pada Peraturan tentang e-liquid dalam rokok elektrik di Inggris sangat berbeda dengan di Indonesia. Ruang lingkup peraturan di Inggris meliputi standart penjualan, saran konsumen, saran penjual dan akibat penggunaan. Sehingga peraturan di Inggris lebih kompleks dibandingkan di Indonesia. Sedangkan di Indonesia belum ada peraturan yang mengakomodasi terkait e-liquid dan rokok elektrik. Selama ini peraturan yang ada di Indonesia terkait rokok konvensional dan tembakau lainnya. Oleh karena itu menyebabkan kekosongan hukum. Sehingga terdapat beberapa kasus mengenai pengunaan e-liquid dan rokok elektrik di Indonesia. Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis normatif, dengan spesifikasi pendekatan perundang-undang dan pendekatan perbandingan.Kata Kunci: Perlindungan Konsumen, E-Liquid, Rokok Elektrik ABSTRACT This research studies issues regarding the protection given in the use of e-liquid in electric cigarettes in Indonesia, which is not regulated in the laws in Indonesia regarding consumer protection in the use of e-liquid in electric cigarettes. Departing from the above issue, this research investigates: (1) how are the regulations regarding the forms of consumer protection over the use of e-liquid between Indonesia and Britain analyzed and compared? (2) what type of legal protection is given to the consumers of e-liquid in electric cigarettes? This research reveals that consumer protection regarding the consumption of e-liquid electric cigarettes is not yet regulated in the positive law in Indonesia. Thus, this research compared the two countries, Indonesia and Britain, since the latter regulates the use of e-liquid in electric cigarettes and clearly and strictly controls the use of the e-liquid. However, there are some harmful effects following the use of e-liquid, but no research has been conducted on the liquid since National Agency of Drug and Food Control (BPOM) does not have the authority to conduct the research. This research is possible to conduct when regulatory provisions are made to regulate the substances composing e-liquid. These regulatory provisions are expected to give legal certainty guaranteed by the state for e-cigarette smokers and e-liquid consumers. Keywords: Consumer Protection,  E-Liquid,  E-Cigarettes